2014
DOI: 10.7150/ijbs.7744
|View full text |Cite
|
Sign up to set email alerts
|

Genome Wide Screening of Candidate Genes for Improving Piglet Birth Weight Using High and Low Estimated Breeding Value Populations

Abstract: Birth weight is an economically important trait in pig production because it directly impacts piglet growth and survival rate. In the present study, we performed a genome wide survey of candidate genes and pathways associated with individual birth weight (IBW) using the Illumina PorcineSNP60 BeadChip on 24 high (HEBV) and 24 low estimated breeding value (LEBV) animals. These animals were selected from a reference population of 522 individuals produced by three sires and six dam lines, which were crossbreds wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 71 publications
0
25
0
Order By: Relevance
“…Additional selection signature has been identified in PEBP4 gene region (placed on SSC14) in Turopolje breed as significant signals were obtained by eROHi and iHS analyses. Assuming that the necessary data become available, future work may wish to take a more comprehensive approach, at least for the relatively large Black Slavonian population, by estimating breeding values for traits of conservation interest and combining those estimates with F ST values to detect conservation-relevant SNPs (Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Additional selection signature has been identified in PEBP4 gene region (placed on SSC14) in Turopolje breed as significant signals were obtained by eROHi and iHS analyses. Assuming that the necessary data become available, future work may wish to take a more comprehensive approach, at least for the relatively large Black Slavonian population, by estimating breeding values for traits of conservation interest and combining those estimates with F ST values to detect conservation-relevant SNPs (Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…WDFY3 ( WD repeat and FYVE domain containing 3 ) has been identified to be associated with birth weight in piglets and might be involved in embryonic or fetal development in pigs (Zhang et al . ). FER1L6 ( fer‐1 like family member 6 ), which was found to affect the pattern of marble marbling score in Korean cattle, also has been suggested as a candidate gene affecting beef quality (Ryu & Lee ).…”
Section: Significant Snps Identified For Carcass Weight (Cw) In Chinementioning
confidence: 97%
“…With the widespread use of customized single nucleotide polymorphism (SNP) arrays, an increasing number of potential markers have been identified by genome-wide association study (GWAS). Wang X. et al (2016) found over two hundred SNPs associated with birth weight by using first parity sows whose offspring had extreme birth weights; Zhang et al (2018) identified 17 genomic regions associated with birth weight; Wang et al (2017) found 12 SNPs that were significantly associated with piglet uniformity; and 27 differentially selected regions associated with the birth weight of piglets were detected by Zhang et al (2014). However, a birth weight GWAS of Large white pigs by Wang et al (2018) was unable to determine any significant loci.…”
Section: Introductionmentioning
confidence: 99%